1999
DOI: 10.1161/01.atv.19.9.2189
|View full text |Cite
|
Sign up to set email alerts
|

Coronary and Aortic Calcification Among Women 8 Years After Menopause and Their Premenopausal Risk Factors

Abstract: Abstract-In the Healthy Women Study, the relationship between cardiovascular risk factors measured premenopausally at age 48, use of hormone therapy, and coronary and aortic calcification at age 58 were evaluated among 169 women. Approximately 63% of women had no coronary calcification, but only 29% had no aortic calcification. Coronary calcification and aortic calcification were positively correlated with each other. There was a very strong association between low density lipoprotein cholesterol (LDL-C) level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 132 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…There was no gender difference in PXE, in contrast to the controls where LLAC was more common in men. As expected, the menopausal status was characterized by a higher prevalence of LLAC [19] but it was not influenced by PXE. The prevalence of AC in our study was much higher than the prevalence of 31% reported in a previous semi-quantitative evaluation of AC based on standard X-ray [7], possibly due to the greater accuracy of CT scans in detecting smaller amounts of calcification.…”
Section: Discussionsupporting
confidence: 81%
“…There was no gender difference in PXE, in contrast to the controls where LLAC was more common in men. As expected, the menopausal status was characterized by a higher prevalence of LLAC [19] but it was not influenced by PXE. The prevalence of AC in our study was much higher than the prevalence of 31% reported in a previous semi-quantitative evaluation of AC based on standard X-ray [7], possibly due to the greater accuracy of CT scans in detecting smaller amounts of calcification.…”
Section: Discussionsupporting
confidence: 81%
“…Among women aged 50 to 59 years at baseline in the WHI E‐Alone Trial, the WHI‐CACS showed that randomization to E‐Alone versus placebo resulted in lower odds of CAC measured ≈8.7 years after baseline, independent of CVD risk factors also associated with subsequent CAC 5. The long incubation period for CAC has been demonstrated by longitudinal studies, showing stronger associations with risk factors measured 11 to 20 years before CAC scan than to concurrently measured risk factors 11, 12, 13. As hypothesized, the association of higher CAC with subsequent CVD events and mortality was not modified by prior randomization to E‐Alone versus placebo and not attenuated by randomized treatment or baseline CVD risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical meaningful cutoff values of aortic calcium scores in the healthy population are unknown, though some investigators use cut points of 100, 300 or 400 14,42 . We used cutoff points of 0, 100 and 400 for baseline aortic calcium, and 0, 10 and 100 for the annual change.…”
Section: Discussionmentioning
confidence: 99%